Structural and biochemical characterization of the N‐terminal domain of flocculin Lg‐Flo1p from Saccharomyces pastorianus reveals a unique specificity for phosphorylated mannose. (24th January 2013) - Sim, Lyann; Groes, Magnus; Olesen, Kjeld; Henriksen, Anette
Abstract : The mechanism of yeast flocculation is generally considered to be mediated through the interaction of cell surface flocculins and mannan carbohydrates. In the present study, the crystal structure of the soluble 25‐kDa lectin domain of flocculin 1 from brewer's yeast (Lg‐Flo1p) was resolved to 2.5 Å, and its binding specificity towards oligosaccharides was investigated by fluorescence spectroscopy. Lg‐Flo1p displays broad specificity towards sugars and has a 14‐fold higher affinity for mannose 1‐phosphate and glucose 1‐phosphate compared to their unphosphorylated counterparts. Based on the results of a structural analysis, we propose that this higher affinity is the result of a charge interaction with a lysine residue in a carbohydrate‐binding loop region, NAKAL, unique to NewFlo type flocculins. This raises the possibility of a unique mechanism of flocculation in NewFlo type yeast, which recognizes phosphorylated cell surface mannans. Database: Structural data have been deposited in the Protein Data Bank under accession number 4GQ7. Abstract : The crystal structure of the 25 kDa lectin domain of Lg–Flo1p flocculin from brewer's yeast was solved and its binding specificity towards oligosaccharides investigated. Lg‐Flo1p has a 14‐fold higher affinity for mannose‐1‐phosphate and glucose‐1‐phosphate, compared to their unphosphorylated counterparts. We propose that this higher affinity is due to charge interaction in a carbohydrate binding region unique to NewFlo type flocculins